Slice by Slice : The Story of Pizza - Beaver, Simon (NewYork Cambridge University, 2014)
Everyone loves a good pizza ! But where did pizza begin? Is it good for us? Learn all about one of our favorite foods.
Cambridge Discovery Education Interactive Readers are the next generation of graded readers - captivating topics, high-impact video, and interactive exercises designed to motivate and engage.
Glossary, Contents.
Keywords: English language; Pre-Intermediate Level; Pizza